Changes in renal function associated with oral emtricitabine/tenofovir disoproxil fumarate use for HIV pre-exposure prophylaxis - Marc M. Solomon (2018)
Objective: Tenofovir disoproxil fumarate (TDF) pre-exposure prophylaxis decreases sexual acquisition of HIV infection. We sought to evaluate the renal safety of TDF in HIV-uninfected persons. Design and methods: The Iniciativa Profilaxis Pre-Exposición (iPrEx) study randomly assigned 2499 HIV-seronegative men and transgender women who have sex with men (MSM) to receive oral daily TDF coformulated with emtricitabine (FTC/TDF) or placebo. Serum creatinine and phosphorus during randomized treatment and after discontinuation were measured, and creatinine clearance (CrCl) was estimated by the Cockcroft- Gault equation. Indicators of proximal renal tubulopathy (fractional excretion of phosphorus and uric acid, urine protein, and glucose) were measured in a substudy. Results: There was a small but statistically significant decrease in CrCl from baseline in the active arm, compared to placebo, which was first observed at week 4 (mean change: -2.4 vs. -1.1 ml/min; P=0.02), persisted through the last on-treatment visit (mean change: + 0.3 vs. + 1.8 ml/min; P=0.02), and resolved after stopping pre-exposure prophylaxis (mean change: -0.1 vs. 0.0 ml/min; P=0.83). The effect was confirmed when stratifying by drug detection. The effect of FTC/TDF on CrCl did not vary by race, age, or history of hypertension. There was no difference in serum phosphate trends between the treatment arms. In the substudy, two participants receiving placebo had indicators of tubulopathy. Conclusions: In HIV-seronegative MSM, randomization to FTC/TDF was associated with a very mild nonprogressive decrease in CrCl that was reversible and managed with routine serum creatinine monitoring. © 2014 Wolters Kluwer Health | Lippincott Williams & Wilkins.